Relationship between reproductive hormones and overweight in 10 to 18 years old boys, a longitudinal study - Autio, Ilmari (My University, 2023)
Context The impact of excess weight on reproductive hormone levels in adolescent boys is poorly known. Objective We investigated how excessive weight during puberty affects reproductive hormone levels by comparing these in normal-weight and overweight/obese boys longitudinally from 10 to 18 years of age. Design This study consisted of randomly selected 100 boys from the Special Turku Coronary Risk Factor Intervention Project (STRIP) in Turku, Finland. Levels of testosterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH), sex hormone-binding globulin (SHBG), anti-Müllerian hormone (AMH), and inhibin B were analyzed in serum samples collected annually at ages 10 to 18 years. This cohort was divided into two study groups (normal weight or overweight) based on their BMI for age (ISO-BMI) both at the start of the study (longitudinal setting) and at each yearly visit (cross-sectional setting). Results Overweight pubertal boys had lower SHBG levels and a higher percentage of calculated free testosterone than their normal-weight counterparts. Furthermore, when the groups were divided into normal-weight and overweight groups at each visit, overweight boys had lower total testosterone and inhibin B levels through adolescence. Being overweight seemed to have little effect on the levels of calculated serum free testosterone, FSH, LH, or AMH. Conclusions Our study links overweight to lower reproductive hormone levels during puberty, especially inhibin B, testosterone and SHBG. This effect may be reversible. Our findings support findings in previous cross-sectional studies, emphasizing the importance of maintaining a healthy weight through adolescence to support optimal future reproductive health.
Keywords: overweight, reproductive hormones, puberty, boys